Using the Stable Isotopic Composition of Heliconoides inflatus Pteropod Shells to Determine Calcification Depth in the Cariaco Basin - Oakes, Rosie L.; Davis, Catherine V.; Sessa, Jocelyn A. (Frontiers in Marine Science, 2021)
Pteropods have been hailed as the ‘canary in the coal mine’ for ocean acidification, however, questions remain about their life history, habitat, and the environmental parameters that the isotopic composition of their shells reflect. In order to use pteropods as recorders of ocean chemistry, it is first necessary to understand where they calcify and how this may change through the year, whether this signal is affected by dissolution, and if shells are retained in the subfossil, and eventually fossil, record. Here we create the first annual record of the stable isotopic composition of shells of the pteropod Heliconoides inflatus in the Cariaco Basin, Venezuela utilizing samples and data from the CARIACO time series. Sixty-four Heliconoides inflatus specimens from 17 sediment trap samples between November 1996 and April 1998, and 22 specimens from the late Holocene-aged CAR2000-MC-2 core were analyzed for shell condition (an assessment of the amount of shell dissolution), size, and carbon and oxygen isotopic composition. Carbon isotopic measurements of juveniles (< 1mm) were more variable than those in adults (>1 mm), suggesting juvenile pteropods likely have a higher growth rate, and therefore different metabolic vital effects, and a more varied diet than adult pteropods. Heliconoides inflatus was found to have an apparent calcification depth of 51.2 ± 34.0 m, suggesting they calcify at the shallowest part of their diurnal migration in the mixed layer (10 - 35 m). H. inflatus shell calcification will therefore only be impacted by changes in water chemistry at mixed layer depths. The shell condition did not impact the stable isotopic composition of the shells in either the sediment trap or core sample, suggesting the potential for using the isotopic composition of pteropod shells as oceanographic proxies when they are preserved. Comparisons between sediment trap and core sample show a 0.5 °C warming that is marginally significant and a significant 0.45 ‰ decrease in δ13C between the late Holocene and the late 1990’s. These measurements reflect changes in oceanic conditions linked to anthropogenic fossil fuel emissions known as the Suess effect, and lay the groundwork for establishing pteropods as paleoceanographic proxies in the future.